Celebrity Endorsement and Beauty Vlogger on Purchase Decisions Mediated by Brand Image - Puspitaningrum, Sari Rahma; Fadhilah, Muinah; Maharani, Bernadetta Diansepti (Jurnal Ilmu Manajemen Advantage, 2024)
The trend of using celebrity endorsement as an advertising medium to attract consumer interest is also being carried out by many companies. This research investigates how endorsers and beauty vloggers influence purchasing decisions through brand image when consumers purchase Scarlett Whitening products in Yogyakarta.. This research is quantitative, and primary data was obtained using a pusposive sampling method. Data was obtained from a questionnaire distribution using google form to 108 respondent in Yogyakarta and than processed using SmartPLS 4 software. From the results of this research, it can be seen that celebrity endorsement have a significant influence on purchasing decisions. Meanwhile, beauty vlogger have no influence on purchasing decisions. Celebrity endorsement have a significant effect on brand image. Beauty vlogger have no influence on brand image. And brand image has an influence on purchasing decisions.